RNA Isolation and leaf CDNA generation of Morinda Citrifolia (Mengkudu) - Jerry, Gerunsin (Universiti Malaysia Sarawak, (UNIMAS), 2007)
The use of herbal medicine are still being used by about 75-85% worldwide especially in developing country. Morinda citrifolia (M. citrifolia) is one of the herbal plants that have been exploited due to its healing properties. For decades, various researches have been conducted to elucidate the medicinal properties of this plant in which this information could be useful for further references in the future. Thus, cDNA library generation is one of the ways to explicate the medicinal value and provide the information where cDNA was first obtained from the isolation RNA. The RNA isolation in this study was employed the method describes by Azevado et al. (2003) with slight modification, which yield a good quality of RNA from leaf of M citrifolia. Subsequently, the extracted RNA was used in cDNA synthesis. Good quality of RNA was yield but unfortunately there was no product for cDNA generation.